Laparoendoscopic single-site surgery for the treatment of different urological pathologies: Defining the learning curve of an experienced laparoscopist - Aly M. Abdel-Karim (Taylor & Francis Group, 2017)
Objectives: To define the learning curve of laparoendoscopic single-site surgery (LESS) of an experienced laparoscopist. Patients and methods: Patients who had LESS, since its implementation in December 2009 until December 2014, were retrospectively analysed. Procedures were divided into groups of 10 and scored according to the European Scoring System for Laparoscopic Operations in Urology. Different LESS indications were done by one experienced laparoscopist. Technical feasibility, surgical safety, outcome, as well as the number of patients required to achieve professional competence were assessed. Results: In all, 179 patients were included, with mean (SD) age of 36.3 (17.5) years and 25.4% of the patients had had previous surgeries. Upper urinary tract procedures were done in 65.9% of patients and 54.7% of the procedures were extirpative. Both transperitoneal and retroperitoneal LESS were performed in 92.8% and 7.2% of the patients, respectively. The intraoperative and postoperative complication rates were 2.2% and 5.6% (Clavien–Dindo Grade II 3.9% and IIIa 1.7%), respectively. In all, 75% of intraoperative complications and all conversions were reported during the first 30 LESS procedures; despite the significantly higher difficulty score in the subsequent LESS procedures. One 5-mm extra port, conversion to conventional laparoscopy and open surgery was reported in 14%, 1.7%, and 1.1% of the cases, respectively. At mean (SD) follow-up of 39.7 (11.4) months, all the patients that underwent reconstructive LESS procedures but one were successful. Conclusion: In experienced hands, at least 30 LESS procedures are required to achieve professional competence. Although difficult, both conversion and complication rates of LESS are low in experienced hands.